INNOVATIVE TECHNOLOGIES IN TEACHING ENGLISH LANGUAGE (Нововведения Cовременного Научного Развития в Эпоху Глобализации: Проблемы и Решения, 2024)
This paper discusses the theoretical basis of the integration of technology and the advantages of using modern technology in English teaching and learning. As modern technology can benefit English education in many ways, it is important to reform the traditional teaching modes by integrating modern technology into English teaching and learning.